Nanomaterials based on cerium oxide nanoparticles for wound regeneration: a literature review - E. V. Silina; N. E. Manturova; A. G. Erokhina; E. A. Shatokhina; V. A. Stupin (Вестник трансплантологии и искусственных органов)
Objective: to analyze data on the synthesis and properties of cerium oxide nanoparticles, as well as the prospects of its application in regenerative medicine for wound healing. Methodology. World literature was reviewed using PubMed, SCOPUS, ResearchGate, CyberLeninck, and Elibrary databases, as well as manual searches for authors and reference lists. Key search terms were «cerium oxide» AND nano* AND (healing OR regeneration OR repair) AND wound». The timeline was from the date of publication through August 2023. Results. The final analysis included 59 sources containing information on the synthesis and size of nanoparticles (and/or other physicochemical characteristics), methodology and results of in vivo and in vitro studies on the efficacy and/or safety of nanoceria for wound regeneration. It is shown that despite the progressive growth of research interest over the last 15 years, the actual use of nanoceria in practical medicine is still not widespread. This is due to a wide variety of non-standardized synthesis methods and conditions, resulting in the variability of physicochemical parameters of nanoparticles (size, form), thereby affecting the safety and biomedical efficacy of nanoceria. Regeneration mechanisms, including the antioxidant-prooxidant, anti-inflammatory and antimicrobial effects of nanoceria, which contribute to accelerated wound healing, are discussed. The severity of the regenerative effects depends on the method and conditions of synthesis, hence the resulting physicochemical characteristics of the nanoparticles. Therefore, after each batch, newly synthesized nanoceria needs physicochemical and biomedical experimental tests. Conclusion. Nanoceria has great potential in tissue engineering for regenerative medicine, particularly for healing of various kinds of wounds. Having developed a technology for standardized synthesis for effective and safe nanoceria (of the right form and size) on a production scale, it can be introduced in medicine, possibly improving the outcomes of treatment of many diseases and pathologies. The authors present conclusions on the results of the study of nanoceria for accelerating qualitative regeneration and the requirements for nanoparticles obtained during synthesis.